THE IMPLEMENTATION OF PROBLEM-BASED LEARNING MODEL TO IMPROVE MATHEMATICS LEARNING OUTCOMES ON SOLID FIGURES MATERIAL FOR FIFTH-GRADE STUDENTS - Hidayat, Wahyu; Musahadah, Musahadah; Zain, Moh. Irawan (PROGRES PENDIDIKAN, 2025)
This study was motivated by the low Mathematics achievement of fifth-grade students at SDN 3 Mataram. From the sample data of students' Mathematics scores, 51.35% (19 out of 37 students) scored below the minimum competency standard (KKM) of 70, with a class average score of 68.37. The research aimed to determine whether the application of the Problem-Based Learning (PBL) model could improve Mathematics learning outcomes on geometry topics for fifth-grade students at SDN 3 Mataram during the 2022/2023 academic year. The classroom action research was conducted in two cycles, with each cycle consisting of the stages of planning, implementing actions, observation, evaluation, and reflection. Data collection methods included learning outcome tests and observation. In Cycle I, the average student learning outcome was 69.19, with a mastery percentage of 71.87%. The teacher activity score in implementing the PBL model was 35, categorized as good, and the student activity score was 34, categorized as active. In Cycle II, there was an improvement: the average student learning outcome increased to 71.48, with a mastery percentage of 84.37%. The teacher activity score rose to 43, categorized as very good, and the student activity score increased to 46, categorized as very active. The findings indicate that the application of the Problem-Based Learning model can effectively enhance Mathematics learning outcomes on geometry topics for fifth-grade students. The implications of this study suggest that PBL can be a valuable instructional approach to address low Mathematics achievement and foster active learning. Educators are encouraged to integrate PBL in their teaching strategies, particularly for challenging mathematical concepts, to improve both student engagement and learning outcomes.